Assessment of cavopulmonary connections by advanced imaging: Value of flat-detector computed tomography - Glöckler, Martin; Koch, Andreas; Halbfass, Julia; Greim, Verena; Rueffer, Andre; Cesnjevar, Robert; Achenbach, Stephan; Dittrich, Sven (Cardiology in the Young, 2013)
Objectives To investigate the impact of flat-detector computed tomography on the clinical assessment of patients with cavopulmonary connections, and to evaluate the obtained diagnostic accuracy and supplementary information, as well as the value of overlaid three-dimensional reconstructions on fluoroscopic images during catheter-based interventions. Methods We analysed 31 consecutive patients retrospectively in whom flat-detector computed tomography was used to visualise the cavopulmonary connection. We investigated patients with cavopulmonary connections either early post-operatively (first group), before converting to a total cavopulmonary connection (second group), and patients with failing total cavopulmonary connection (third group). Flat-detector computed tomography based on a single rotational angiography was used to create a three-dimensional vascular model. The clinical value of flat-detector computed tomography was evaluated using standard categories of diagnostic utility. Used contrast volume and radiation exposure were quantified. Results Within 18 months, flat-detector computed tomography was performed in 31 cases with cavopulmonary connections. The median age was 1.9 years (range 0.3-43 years). In the first group, we found anomalies in 4 out of 8 cases, which led to therapeutic or prophylactic procedures; in the second and third groups, we performed interventions in 14 out of 23 cases. The overall clinical value was always rated superior to conventional biplane angiography. The median dose area product was 91.8 microgray square metres (range 33.0-679.3 microgray square metres). The required contrast medium was 2.08 millilitres per kilogram (range 0.66-4.7 millilitres per kilogram). Conclusion Flat-detector computed tomography improves the diagnostic accuracy in cavopulmonary connections and provides additional diagnostic information, which may lead to therapeutic or prophylactic procedures. Overlaid three-dimensional images on fluoroscopy facilitate and provide security for interventions. © Cambridge University Press 2012.
CRIS-Team Scopus Importer:2023-03-08
Keywords: interventions in congenital heart disease; rotational angiography; Three-dimensional